Age-Related Alterations in the Metabolic Profile in the Hippocampus of the Senescence-Accelerated Mouse Prone 8: A Spontaneous Alzheimer's Disease Mouse Model - Wang, Hualong (J Alzheimers Dis, 2014)
Alzheimer's disease (AD), the most common age-dependent neurodegenerative disorder, produces a progressive decline in cognitive function. The metabolic mechanism of AD has emerged in recent years. In this study, we used multivariate analyses of gas chromatography-mass spectrometry measurements to determine that learning and retention-related metabolic profiles are altered during aging in the hippocampus of the senescence-accelerated mouse prone 8 (SAMP8). Alterations in 17 metabolites were detected in mature and aged mice compared to young mice (13 decreased and 4 increased metabolites), including metabolites related to dysfunctional lipid metabolism (significantly increased cholesterol, oleic acid, and phosphoglyceride levels), decreased amino acid (alanine, serine, glycine, aspartic acid, glutamate, and gamma-aminobutyric acid), and energy-related metabolite levels (malic acid, butanedioic acid, fumaric acid, and citric acid), and other altered metabolites (increased N-acetyl-aspartic acid and decreased pyroglutamic acid, urea, and lactic acid) in the hippocampus. All of these alterations indicated that the metabolic mechanisms of age-related cognitive impairment in SAMP8 mice were related to multiple pathways and networks. Lipid metabolism, especially cholesterol metabolism, appears to play a distinct role in the hippocampus in AD.